Pengaruh beban kerja dan work family conflict terhadap kinerja karyawan: Studi pada Satker Pelaksanaan Jaringan Pemanfaatan air (PJPA) Balai Besar Wilayah Sungai Pompengan Jeneberang di Kota Makassar - Primawalda, Az-zahra Rizqi; Amin, Andi Mustika; Haeruddin, Muh. Ikhwan Maulana; Anwar, Anwar; Aslam, Annisa Paramaswary (Nur Science Institute, 2023)
This research aims to determine the effect of Workload and Work-Family Conflict on employee performance. This research used three data collection methods, namely: observation, interviews, and distributing questionnaires to employees of the Water Utilization Network Implementation Unit (PJPA) of the Pompengan Jeneberang River Area Center in Makassar City with a population of 103 people and a sample of 82 respondents. The data analysis method used in this research is multiple linear regression. The results of the analysis show that workload hurts employee performance, and work-family conflict hurts employee performance.